Incorporating gerontological and geriatrics information into picture books for 9-12 year-old children: A stakeholder engagement design. Issue 1 (2nd January 2023) - Li, Chia-Wei; Chiu, Ching-Ju
ABSTRACT: This study explored the preferences of different stakeholders when translating geriatrics and gerontology concepts into children's picture books, with the aim of developing a feasible model. Following the stakeholder engagement design and qualitative method, three types of stakeholders were enrolled: medical and educational professionals (n = 9), older adults aged over 65 (n = 9), and children aged 9 to 12 (n = 7). Individual interviews and focus groups were used to collect the views of the stakeholders as a basis for revising the picture book, as well as to analyze the opinions of different stakeholders. Results show that medical professionals' recommendations focused on intellectual content (18.0%) and written verbal narratives (16.5%). Education experts tended to recommend textual verbal narratives (18.8%) and storyline (6.0%). Older adults's suggestions focused on story content (6.8%) and included detailed descriptions of older adults. Children's suggestions were focused on plot arrangement (2.3%) and text size (2.3%). Mean scores for the appropriateness of the three picture book materials increased after the stakeholder engagement, with the communication literacy picture book achieved statistical significance ( p = .042). It is concluded that the stakeholder engagement design is a viable development model for achieving intergenerational understanding, realistic and theoretical goals, and bridging heterogeneity across the stakeholders.